2006
DOI: 10.1007/s00464-006-9005-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic effectiveness of percutaneous drainage with antibiotics versus antibiotics alone in the treatment of periappendiceal abscess

Abstract: Percutaneous drainage with antibiotics is a safe and effective way of treating acute perforated appendicitis. The recurrence rate for these patients is relatively low, and very often interval appendectomy is not required. For patients with periappendiceal abscess> or = 3 cm in diameter, antibiotic therapy alone is insufficient and the recurrence rate is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
3
15
1
1
Order By: Relevance
“…Previous studies reported a high success rate of 76~97% for non-surgical treatment. [2][3][4][5][6][7][8] In the present study, there were 3 cases (3.6%) of treatment failure in non-surgical management. Two of them underwent emergent surgery under septic condition due to deterioration of inflammation despite initial antibiotic treatment.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies reported a high success rate of 76~97% for non-surgical treatment. [2][3][4][5][6][7][8] In the present study, there were 3 cases (3.6%) of treatment failure in non-surgical management. Two of them underwent emergent surgery under septic condition due to deterioration of inflammation despite initial antibiotic treatment.…”
Section: Discussionmentioning
confidence: 84%
“…[27][28][29] After successful conservative or/and image-guided drainage management, IA is often not necessary and can safely be omitted, except in patients with recurrent symptoms. 1,2,10,30 However, proponents of IA point to advantages of initial conservative treatment followed by IA; the approach avoids the recurrence of symptoms and the misdiagnosis of alternative pathologies, such as malignancy, tuberculosis, diverticulosis, and Crohn' s disease. 9,10 In our study period, after non-surgical treatment, one patient had appendiceal cancer, and four had Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendicitis has been managed in constrained conditions with antibiotics and bowel rest. However, increased morbidities and recurrent appendicitis have been seen in these patients [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…14 Abscesses larger than 3 cm can be considered serious 15 16 and are unlikely to resolve with antibiotics alone. 17 Open drainage or appendicectomy can lead to an infection of the wound in up to 16% of patients. 18 In all cases of right iliac fossa mass, a carcinoma of the colon should be excluded.…”
Section: Treatmentmentioning
confidence: 99%